2017
DOI: 10.5698/1535-7511-17.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating MicroRNAs in Murine Models: Targeting the Multi-Targeting in Epilepsy

Abstract: MicroRNAs are small noncoding RNAs that work posttranscriptionally to negatively regulate protein levels. They influence neuronal and glial structure and function, neuroinflammatory signaling, cell death, neurogenesis, and other processes relevant to epileptogenesis. Functional studies using oligonucleotide inhibitors (antagomirs) and mimics (agomirs) to modulate microRNAs in rat and mouse models of epilepsy show effects on evoked and spontaneous seizures and attendant neuropathology. The present review summar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…Our unbiased screen for anti-seizure phenotypes identified five antagomirs that protect the brain against prolonged seizures, of which those targeting miR-10a-5p, miR-21a-5p and miR-142a-5p had the most robust effects. This is a substantial addition to the number of miRNAs reported as potential targets for seizure control 20 . It also suggests that many of the upregulated miRNAs in the chronic epilepsy phase may be suppressing targets that would otherwise oppose hyperexcitability.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Our unbiased screen for anti-seizure phenotypes identified five antagomirs that protect the brain against prolonged seizures, of which those targeting miR-10a-5p, miR-21a-5p and miR-142a-5p had the most robust effects. This is a substantial addition to the number of miRNAs reported as potential targets for seizure control 20 . It also suggests that many of the upregulated miRNAs in the chronic epilepsy phase may be suppressing targets that would otherwise oppose hyperexcitability.…”
Section: Discussionmentioning
confidence: 94%
“…Spatio-temporal changes to miRNA expression have been reported in the hippocampus following epileptogenic brain injuries and these persist in established epilepsy 17, 18 . In parallel, in vivo deployment of oligonucleotide miRNA inhibitors (antagomirs) has demonstrated functional roles for a few miRNAs in seizure control and epileptogenesis 19, 20 . It remains unknown how many more miRNAs may be suitable targets in epilepsy.…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, experimental studies have shown that manipulating miRNAs can have strong effects on seizures, attendant neuropathology, and epileptogenesis. More than a dozen miRNAs have now been targeted in experimental models and have been reported to produce changes to evoked and spontaneous seizures . Although coexpression of clusters of miRNAs targeting common pathways has been shown during epileptogenesis, some miRNAs may even act individually as master regulators of this phenomenon.…”
Section: Why Micrornas As Molecular Biomarkers Of Epilepsy?mentioning
confidence: 99%
“…Extensive research has revealed that microRNAs influence brain structure and function by fine-tuning protein levels of genes involved in neuronal morphology, glial responses, neuroinflammation, and other processes. 12,29 We and our collaborators recently identified a microRNA controlling expression of the Kv4.2 mRNA (KCND2) that encodes a dendritically expressed potassium channel that reduces dendritic excitability. 28 More than a dozen microRNAs have now been identified that positively or negatively affect seizure onset or severity during status epilepticus, status epilepticus-induced brain injury, or development of recurrent spontaneous seizures.…”
Section: Noncoding Rnasmentioning
confidence: 99%
“…28 More than a dozen microRNAs have now been identified that positively or negatively affect seizure onset or severity during status epilepticus, status epilepticus-induced brain injury, or development of recurrent spontaneous seizures. 12,29 We and our collaborators recently identified a microRNA controlling expression of the Kv4.2 mRNA (KCND2) that encodes a dendritically expressed potassium channel that reduces dendritic excitability. 30 Manipulating miR-324 altered surface expression of the potassium channel in neurons, and reducing miR-324 expression rendered mice refractory to status epilepticus, delaying seizure onset and severity and reducing hippocampal damage.…”
Section: Noncoding Rnasmentioning
confidence: 99%